Effect of heating temperature on preparation ZNO/cellulose composites using hydrothermal method - Khairil Naim Sukarno (2024)
The study investigates the impact of heating temperature on the structural, morphological, and optical properties of the composites. The XRD pattern of the composites prepared at different temperatures reveal significant insights into the crystallinity and structural properties of the composites. The observed increase in peak intensity with higher heating temperatures suggests enhanced crystallinity, indicating improved interaction between cellulose and ZnO. The SEM images of the composites show that the morphology of the composites changes with increasing heating temperature, with the composites prepared at higher temperatures exhibiting a more uniform and compact structure. The UV-Vis spectra of the composites demonstrate that the composites exhibit efficient UV light absorption and selectivity, with the absorbance increasing with increasing heating temperature. Overall, the study provides valuable into the synthesis and characterization of ZnO/cellulose composites using the hydrothermal method and highlights the potential of the composites for various applications, including UV sensors and biomedical devices.